Leadership and technostress: a systematic literature review - Tim Rademaker; Ingo Klingenberg; Stefan Süß (Management Review Quarterly, 2023)
With the growing use of digital technologies at work, employees are facing new demands. Digital technologies are also changing how leaders and followers interact. Leadership must adapt to these changes and find ways to reduce the demands of digital work for their followers so they maintain their capacity for and motivation to work. Against this background, we analyze the impact leadership has on technostress by conducting a systematic literature review. An electronic search was based on 13 databases (ACM Digital, AIS eLibrary, APA PsychInfo, EBSCO, Emerald Insight, Jstor, Pubmed, SAGE, ScienceDirect, Scopus, Taylor & Francis Online, WISO, and Web of Science) and was carried out in October 2023. We identified 1725 articles—31 of which met the selection criteria. Thirteen more were identified in a backward search, leaving 44 articles for analysis. The conceptual analysis reveals that empowering and supportive leadership can decrease follower technostress. Leadership that emphasizes high availability expectations, task orientation and control can increase technostress and technostress-related outcomes. Furthermore, leadership's impact on follower technostress is influenced by how ICTs are being used to convey leadership. We synthesize seven analytical themes of leadership among the technostress literature and derive them into the three aggregated dimensions which serve as the foundation of a conceptual model of leadership's impact on follower technostress: technostress-increasing leadership, technostress-decreasing leadership, and technology-enabled leadership. Furthermore, we formulate avenues for future research.
Keywords: O33; M54; I19; 650; Technostress; Digital stress; Leadership; Followership; Digital work; Systematic literature review